Chess opening workshop / Siti Zaharah Mohd Ruslan and Norlida Othman - Mohd Ruslan, Siti Zaharah; Othman, Norlida (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The "CHESS OPENING WORKSHOP" was held on 10 June 2023 from 8:30 am to 1:00 pm at the College of Computing, Informatics, and Mathematics UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah. A total of 42 participants from SK Seri Pilah, SK Jempol, SK Tengkek, SRITI Alfattah, SRITI Al-Amin Juasseh, SK Tunku Laksamana Nasir, SK Kuala Pilah, SK Dato' lnas, SK Tunku Munawir and SK Taman Paroi Jaya joined the workshop. The main objective of the workshop was to increase participants' knowledge, and skills in mastering techniques of chess games and giving exposure to the chess match situation. In addition, this program aims to provide an opportunity to further strengthen the existing skills of participants in preparation for participating in the Negeri Sembilan MSSM Chess Tournament. This activity is conducted face-to-face in Seminar Room 3. A participation fee of RM25 is also charged to each participant.